Understanding mechanotransduction in the distal colon and rectum via multiscale and multimodal computational modeling - Shokrani, Amirhossein; Almasi, Ashkan; Feng, Bin; Pierce, David M. (Journal of the mechanical behavior of biomedical materials, 2024)
Visceral pain in the large bowel is a defining symptom of irritable bowel syndrome (IBS) and the primary reason that patients visit gastroenterologists. This pain is reliably triggered by mechanical distension of the distal colon and rectum (colorectum). Consequently, the process of mechanotransduction by sensory afferents, responsible for translating mechanical colorectal stimuli into neural action potentials, plays a central role in IBS-related bowel pain. In this study, we aim to enhance our understanding of colorectal mechanotransduction by combining experimental findings in colorectal biomechanics and afferent neural encoding within a comprehensive computational simulation framework. To achieve this, we implemented a three-layered, fiber-reinforced finite element model that accurately replicates the nonlinear, heterogeneous, and anisotropic mechanical characteristics of the mouse colorectum. This model facilitates the computation of local mechanical stresses and strains around individual afferent endings, which have diameters on the micron-scale. We then integrated a neural membrane model to simulate the encoding of action potentials by afferent nerves in response to microscopic stresses and strains along the afferent endings. Our multiscale simulation framework enables the assessment of three hypotheses regarding the mechanical gating of action potential generation: (1) axial stress dominates mechanical gating of mechanosensitive channels, (2) both axial and circumferential stresses contribute, and (3) membrane shear stress dominates. Additionally, we explore how the orientation of afferent endings impacts neural encoding properties. This computational framework not only allows for the virtual investigation of colorectal mechanotransduction in the context of prolonged visceral hypersensitivity but can also guide the development of new experimental studies aimed at uncovering the neural and biomechanical mechanisms underlying IBS-related bowel pain. [Display omitted] •Established a novel multiscale model to simulate mechanotransduction in IBS pain.•Integrated colorectal biomechanics with neural fiber encoding into a multiscale model.•Evaluated three hypotheses on stresses causing mechanical gating of afferent fibers.•Analyzed the impact of orientation of afferent endings on the neural encoding.•Facilitate new studies to reveal neural and biomechanical mechanisms of IBS pain.